PMO-104 The use of faecal elastase in a district general hospital. (28th May 2012) - Tash, E; Subhani, J; Lindo, D; Gertner, D; Joy, M; Carrigan, R; Everitt, T; Munuswamy, P
Abstract : Introduction: Faecal elastase 1 (FE) is a proteolytic enzyme secreted by the acinar cells of the pancreas. Its determination is a highly sensitive and specific tubeless pancreatic function test. The 2003 BSG guidelines were compiled to minimise investigations and maximise positive diagnoses for patients with diarrhoea lasting more than 4 weeks. 1 We analysed the appropriate use of the faecal elastase test and its correlation with symptoms in a large district general hospital. Methods: This retrospective study included all patients who had a FE requested from April 2009 to March 2010. Data were analysed for indication, symptoms, outcome of the test, follow-up, other investigations and the use of creon. Results: Over a period of 1 year, 121 patients had a FE requested. Patient notes and laboratory information was only available for a total of 101 patients. Data were collected from these notes for further analysis. 19 patients (19%) had pancreatic insufficiency with low FE levels (ranging <15–144). 82 patients had normal FE levels (>500). In patients with a low FE levels, 12 patients had diarrhoea (63%), steatorrhoea (21%), abdominal pain (26%), weight loss (47%), alcohol history (15%), history of pancreatitis in (53%) and none of these patients had abdominal distention, flatulence or offensive stools. 58% in the low FE group had treatment with creon. A logistic regression analysis was performed on three symptoms; diarrhoea, steatorrhoea and previous history of pancreatitis. History of pancreatitis was statistically significant with an OR of 10.21, for faecal elastase insufficiency. Conclusion: In our study group we found that a previous history of pancreatitis was a strong predictor of a low faecal elastase. Though statistically not significant, patients with diarrhoea, steatorrhoea and weight loss, do benefit from FE testing. Competing interests: None declared. Reference: 1. Thomas PD, et al. Guidelines for the investigation of chronic diarrhoea. 2nd edn. Gut 2003;52 (Suppl V):v1–5.